2021
DOI: 10.3390/rs13040678
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of DTM Source Data on the LS Factors of the Soil Water Erosion Model Values with the Use of GIS Technology

Abstract: Counteracting soil degradation is one of the strategic priorities for sustainable development. One of the most important current challenges is effective management of available resources. Multiple studies in various aspects of soil water erosion are conducted in many research institutions in the world. They concern, among others, the development of risk estimation models and the use of new data for modelling. The aim of the presented research was a discussion on the impact of the accuracy and detail of elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…However, slope and aspect also receive attention in numerous papers. Their joint analysis (e.g., [38,40,94,[97][98][99][100]) is usual, but there are also cases in which only one of them is analyzed (e.g., [39,62,101,102]). The analysis of the slope is more frequent than that of the aspect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, slope and aspect also receive attention in numerous papers. Their joint analysis (e.g., [38,40,94,[97][98][99][100]) is usual, but there are also cases in which only one of them is analyzed (e.g., [39,62,101,102]). The analysis of the slope is more frequent than that of the aspect.…”
Section: Discussionmentioning
confidence: 99%
“…From this information a planimetric accuracy bound of the original source can be inferred, but not the altimetric accuracy because it does not always have a direct relationship with the planimetric accuracy. In some papers, the evaluation of slope and orientation is proposed instead of the elevation (e.g., [38][39][40][41][42]), and the situation regarding the accuracy of the reference data is even more obscure. It is usual to establish conditions or limitations on references.…”
Section: The Reference Datamentioning
confidence: 99%
“…Previous research has shown that herbaceous plants in the study area primarily rely on soil moisture within the 0 to 40 cm depth range [ 33 , 34 ]. Furthermore, it has been observed that approximately 80% of the roots of sand-binding shrubs are distributed between 40 and 200 cm, with about 10% of the roots extending between 200 and 300 cm [ 35 , 36 ]. Building upon these findings, this study categorized soil moisture into three layers for analysis: the surface layer (0–40 cm), the middle layer (40–200 cm) and the deep layer (200–300 cm) to investigate its relationship with topographic and vegetation factors.…”
Section: Methodsmentioning
confidence: 99%
“…The lowest mean LS for the DMR 20 is calculated from the W-S, while the highest mean The input data on the relief is very important for the USLE-2D method. When calculating the LS-factor, the resolution of the pixel with the altitude data plays a key role (Fijałkowska, 2021;Michalopoulou et al, 2022). A high resolution (1x1m) resulted in very low LSfactor values in this case.…”
Section: Comparison Of the Ls -Factorsmentioning
confidence: 96%